Variability of Growth, Yield and Nutrient Concentration in Moth Bean (Vigna aconitifolia (Jacq) Marechal) on Arid Lands - Kumar, D; Tarafdar, J C; Kumar, Praveen (Annals of Arid Zone, 2016)
Study on thirty diverse genotypes of moth bean Virna aconitifolia (Jacq) Marechall. conducted under arid conditions, revealed enormous genetic variability for grain yield and the concentration of P. K. Fe. Mg and Mn nutrients in aboveground plant parts at flowering. High estimates of hroad sense heritability afld genetic advance observed for P. K and Fe concentrations and grain yield suggested that these traits would respond to simple selection. Significant negative correlations of grain yield with flowering and maturity periods revealed the importance of short seasoned strains for arid lands. Significant positive association of Zn concentration with grain yield was mainly due to its maximum direct positive effect (2.415). whereas the signiticant positive correlation between P concentration and grain yield was possibly due to indirect effect via Zn concentration. Thus. concentrations of P and Zn appear crucial for moth hean in abrupt arid conditions.